Analytical evaluation of lateral rail unevenness on high-speed railway bridge after transversal seismic shaking. (15th September 2022) - Lai, Zhipeng; Jiang, Lizhong
Highlights: The residual deformations in the HSRTBS subjected to an earthquake mainly lay in the sliding layer and the bridge bearings. An analytical model of the mapping between the rail unevenness and the residual deformations in the HSRTBS has been developed. The residual deformations of different components in the HSRTBS subjected to an earthquake contribute differently to the post-earthquake rail unevenness. Abstract: China has the largest network of high-speed railway (HSR) lines in the world. Since most of China's territories are within seismic zones, many HSR lines are under the threat of earthquakes. The HSR lines in China have only been operating for a few years, and the majority of the built HSR bridges have not been subjected to seismic shaking. The key function of the HSR track-bridge system (HSRTBS) is to ensure the safe and comfortable operation of the high-speed trains, while the rail unevenness presents a major threat to the train operation on the HSRTBS. When the HSRTBS is subjected to an earthquake, the residual deformations in the HSRTBS cause the rail unevenness to deteriorate. In this study, a technique to address the lateral rail unevenness on the HSRTBS after transversal seismic shaking has been developed. By using OpenSEES (https://opensees.berkeley.edu/ ), a refined nonlinear finite element (FE) model of an HSRTBS has been developed in the first place. Then, the distribution of the lateral residual deformations in the HSRTBS has been assessed. Thereafter, an analytical model of the mapping between the rail unevenness and the lateral residual deformations in the HSRTBS has been established. According to the analytical model, the rail unevenness corresponding to the lateral residual deformations in the HSRTBS has been evaluated. The superposition of the mapped rail deformations accords with the residual rail deformations obtained from the FE results. The framework developed in this study provides an effective methodology to evaluate the contributions of lateral residual deformations of different components to the lateral rail unevenness on the HSRTBS after seismic shaking.